Estudos de pré-formulação em losartano potássico através das técnicas de análise térmica e espectroscópicas - Pires, Sumaia Araújo (2012)
This study aimed to apply thermal analysis techniques in the study of drug-excipient compatibility losartano potassium (LST) - an antihypertensive, class of antagonists of angiotensin II, used to treat hypertension. Differential Scanning Calorimetry (DSC), thermogravimetry (TG), X-ray diffraction powder Absorption Spectrometry in the Infrared Region East and scanning electron microscopy were used to characterize the losartano potassium. For the purpose of evaluating possible interactions between the components of each binary mixture 1:1 losartano-carriers, excipients and each mixture were evaluated by X-ray diffraction powder, TG, DSC and Raman spectroscopy. The excipients were studied starch, lactose monohydrate (LAC), magnesium stearate (EM), hydroxypropylcellulose (HPC), croscarmellose sodium (CS), polyvinylpyrrolidone (PVP), talc, microcrystalline cellulose (MC), talc, hydroxyethylcellulose (HEC) , carboxymethylcellulose (CMC) and povidone (PD). The results of DSC and TG suggested that the excipients HEC, LAC, CS, HPC, EM, PVP show possible interactions with LST was confirmed by the disappearance of the event or shift transition of crystalline drug. The compatibility study using X-ray diffraction powder indicated that LST remained in the same polymorphic form I in the presence of excipients analyzed, except when mixed with the talc. The analysis by Raman spectroscopy showed chemical incompatibility with excipients EM, CMC, LAC e HEC. Tablets were prepared containing the form I and II which exhibited significantly different dissolution profile. Furthermore, it can be shown, with the construction of a calibration curve, the DSC is a useful technique for quantifying also polymorphic.